ديوان - بن صالح, أبو الحسن علي (المؤسسة الوطنية للكتاب, 1984)
Keywords: Poésie -- Mzab

ديوان أبي اليقظان - أبو اليقظان, إبراهيم بن عيسى (جمعية التراث, 1989)
Keywords: Poésie -- Mzab

... sur un Poème Arabe - Moriaz, Jean (Le Saharien, 1987)
Keywords: Poésie -- Mzab

مفدي زكرياء شاعر النضال والثورة - ناصر, محمد صالح (جمعية التراث, 1989)
Keywords: Poésie -- Mzab

إليادة الجزائر - زكرياء, مفدي (المؤسسة الوطنية للكتاب, 1987)
Keywords: Poésie -- Mzab

Shaqā’iq al-Nuʿmān ʿalà Sumūṭ al-Jumān fī Asmā’ Shuʿarā’ ʿUmān - Khuṣaybī, Muḥammad b. Rāshid b. ʿUzayyiz al- (1984)
After the table of contents of vol. 1, thirteen pages with panegyrics by: ʿAbdl. b. ʿAlī al-Khalīlī, Mūsà b. Sālim al-Ruwāḥī, Ḥabrās b. Shubayṭ, Hilāl b. Sālim al-Siyābī, Abū Surūr [Ḥumayyid b.ʿAbdl. b. Ḥumayyid b. Surūr al-ʿUmānī], Aḥm. b. ʿAbdl. al-Ḥārithī, Hāshim b. ʿĪsà al-Ṭā’ī, Aḥm. b. Ḥamad al-Khalīlī, Muftī of Oman. Then five pages from the MS of the author, with a portrait of him. The Qaṣīda with the title of the book is on pp. 396-413 of vol. 1. The work was completed 4 Rab. II 1403/1983. The author lists Omani poets from the earliest times to the 21st century, with emphasis on the period from the 13th/19th century onwards. He gives examples of their poetry, says a few words on every poet, and on occasion makes short excursions on certain events, areas, tribes and sub-sections of tribes. In volume 2 for example, there is an excursion on the conquest of Oman by Mālik b. Fahm b. Ghānim b. Dūs al-Azdī al-Dūsī and his death at the hand of his son Sulayma when he was 120 years old (pp. 173-178). In this same volume, on pp. 191-197, he lists the Nabāhina kings until 1024/1615, and, speaking of the Nabāhina, he comes to speak of Ḥimyar b. Nāṣir b. Sayf b. Sul. b. Ḥimyar al-Nabhānī (1291-Jum. II 1338/1874-5 - 1920), whose father died 19 Dhū ‘l-Qaʿda 1293/1876, and on the discord between Sul. b Ḥimyar [al-Riyāmī] (d. 1998, a few years after his return to Oman from exile. See Mershen 2001) and Imam Ghālib b. ʿAlī al-Hinā’ī, (Imam 1954), who had to flee to Dammam in Saudi Arabia a few years later, together with his brother Ṭālib (who died in Cairo in 1401/1980-1) when Sultan Saʿīd b. Taymūr conquered the interior of Oman. On pp. 201-216 the author gives a list of the Imams of the Āl Yaḥmad and the Banū Kharūṣ (who are from the Āl Yaḥmad), who started governing Oman after the Julanda. On pp. 221-226, a list of the Yaʿāriba Imams, then of the rulers of the Āl Bū Saʿīd (pp. 226-242), with on pp. 242-243 a few words on Barghash b. Saʿīd al-Būsaʿīdī, Sultan of Zanzibar from 1870 to 1888. Khuṣaybī arranged the poets he lists in Ṭabaqas. The first Ṭabaqa are poets with Dīwāns, either printed or in manuscript, Majmūʿas or Muqaṭṭaʿāt. The second Ṭabaqa is of poets with Majmūʿas of poetry or Muqaṭṭaʿāt, but with almost no Dīwāns. The third Ṭabaqa are poets who composed panegyrics for Imams, kings and Emirs, with Dīwāns, printed or not, Majmūʿāt or Muqaṭṭaʿāt. The fourth Ṭabaqa is composed of the most famous poets, whose poems have been noted down and printed. Then, in the fifth Ṭabaqa, the author lists brilliant poets and scholars who wrote Urjūzas on al-Adyān wa’l-Aḥkām, Siyar, etc. In the sixth Ṭabaqa we see scholars and judges in the 14th/20th century, who wrote poems on all sorts of subjects, but who wrote no Urjūzas on al-Adyān wa’l-Aḥkām. Finally, in the seventh Ṭabaqa, Khuṣaybī lists poets who live in the 15th/21st century and wrote mainly questions and answers in rhyme on Fiqh, literature, etc. As for his sources, Khuṣaybī mentions them seldomly. Apart from the information he gathered himself, he quotes from Sālimī: Tuḥfat al-Aʿyān, Sālimī: Nahḍat al-Aʿyān, Ibn Ruzayq: al-Fatḥ al-Mubīn, Ibr. b. Saʿīd al-ʿIbrī’: Tabṣirat al-Muʿtabarīn, Anonymous: Kashf al-Ghumma. Although many of the poets listed (especially those living into the 21st century) produced poetry of a pure artistic nature, I copied the poets Khuṣaybī lists in this bibliography, because many of them were in their poetry inspired by local historical events, composed poems in praise of Imams and Sultans, and other persons or tribes or places. Zubayr 1991 clearly must have used Khuṣaybī’s work, and he is also quoted in Fārisī, Nāṣir b. Manṣūr 1994.
Keywords: Poésie -- Mzab

Moufdi Zakaria "l'odyssée d'un poète" - Khorsi, Samia (Révolution Africaine, 1986)
Keywords: Poésie -- Mzab